2007
DOI: 10.1245/s10434-007-9556-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proliferation by Omega-3 Fatty Acids in Chemoresistant Pancreatic Cancer Cells

Abstract: n-3 FA treatment is specifically associated with inhibition of proliferation in these four pancreatic cell lines irrespective of varied gemcitabine resistance. An experimental paradigm to screen for potential contributory mechanism(s) in altered pancreatic cancer cellular proliferation was defined, and using this approach the co-administration of n-3 FA with GEM inhibited GEM-induced NF-kB activation and restored apoptosis in the MIA PaCa-2 cell-line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 23 publications
1
44
1
1
Order By: Relevance
“…3A). Third, although piceatannol has been reported to inhibit FAK, src, PI3K and IB/NF-B kinases (Ashikawa et al, 2002;Choi et al, 2010;Law et al, 1999), inhibition of these kinases has been shown to retard the proliferation of both syk-positive and syknegative lines used in this study (Hering et al, 2007;Hochwald, et al, 2009;Ito et al, 2003;Perugini et al, 2000). Together, these points demonstrate that the antiproliferative effect of piceatannol reported here is likely restricted to the inhibition of syk itself.…”
Section: Syk-dependent Regulation Of Cell Growth Requires Syk Kinase supporting
confidence: 45%
“…3A). Third, although piceatannol has been reported to inhibit FAK, src, PI3K and IB/NF-B kinases (Ashikawa et al, 2002;Choi et al, 2010;Law et al, 1999), inhibition of these kinases has been shown to retard the proliferation of both syk-positive and syknegative lines used in this study (Hering et al, 2007;Hochwald, et al, 2009;Ito et al, 2003;Perugini et al, 2000). Together, these points demonstrate that the antiproliferative effect of piceatannol reported here is likely restricted to the inhibition of syk itself.…”
Section: Syk-dependent Regulation Of Cell Growth Requires Syk Kinase supporting
confidence: 45%
“…Multiple labs, including our own, have reported that the PANC-1 cell line is more chemoresistant than other cell lines, often exhibiting higher IC 50 values. [24][25][26][27][28][29] In this study, we also demonstrate that D-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (PDMP), a glucosylceramide synthase inhibitor and gemcitabine, a nucleoside analog, enhance the antitumor activity of Lip-C 6 . We show that the biological effect of Lip-C 6 is achieved through inhibition of Akt phosphorylation, and suggest that the distinctive action of the anti-metabolite gemcitabine can be used to prime the PANC-1 cells to the action of Lip-C 6 .…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, NF-kB activation leads chemoresistance to gemcitabine, the most widely used first-line chemotherapeutic drug in human pancreatic tumors (11). To determine whether the increase observed in RAGE expression was also responsible for oxidative injury-mediated activity of NF-kB, we determined the activity of NF-kB using a luciferase reporter assay and the location of NF-kB p65 by immunofluorescence analysis in pancreatic cancer cells transfected with RAGE-shRNA and control shRNA.…”
Section: Suppression Of Rage Expression Decreases the Activity Of Nf-mentioning
confidence: 99%